Comparison of carotid artery dimensions and lesion length measured by B‐mode ultrasonography and quantitative angiography in patients with severe stenosis undergoing percutaneous revascularization. Issue 5 (22nd January 2014) - Harmon, Laura; Boccalandro, Fernando
ABSTRACT Background To evaluate the correlation and agreement of the carotid artery landmarks necessary for carotid artery stenting obtained by B‐mode ultrasonography (BMU), and by quantitative angiography (QCA) in patients with severe carotid artery stenosis. Methods In 75 patients undergoing carotid artery stenting, the distal common (CCA), proximal internal (ICA) carotid artery diameter, and lesion length were measured preoperatively by BMU, and intraoperatively by QCA. Results In 96% of the subjects, BMU imaging was adequate for interpretation. BMU and QCA Pearson correlation and Lin concordance coefficients were 0.75 (p < 0.001) and 0.959 (95% CI: 0.930 – 0.996), respectively, for CCA diameter, 0.88 (p < 0.001) and 0.954 (95% CI: 0.928‐0.983), respectively, for ICA diameter, and 0.62 (p < 0.001) and 0.734 (95% CI: 0.719‐0.760), respectively, for lesion length, with a 0.765 bias correction factor and a wider data scatter by Bland Altman plots showing shorter lesion length by BMU than by QCA. Conclusions In patients with carotid artery stenosis, BMU can provide reliable distal CCA and proximal ICA diameters in comparison with QCA, whereas lesion length measured by BMU has an acceptable correlation, but a poor agreement with QCA. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound42:270–276, 2014